(untitled) (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The study was conducted to investigate the effect of mastitis on post-partum conception in crossed cows (Local x Friesian or Sahiwal x Friesian) in Chittagong area of Bangladesh. Materials and methods: A total of 100 lactating cows were randomly selected from thirteen small and medium size commercial dairy farms. The cows were reared under traditional feeding and management systems. Age and number of parity of the cows were 2.5 to 6 years and 1-5, respectively. On-farm California Mastitis Test (CMT) and Whit Slide Test (WST) were performed with the milk samples to diagnose mastitis. Besides, productive and reproductive data were recorded by examining the animals and interviewing the farmers. Results: The incidence of mastitis was significantly (P=0.037) higher (76% for CMT and 62% for WST) in 3.5-4.5 years old cows and lower (P=0.037) (47% for CMT) in 2.5-3.5 years old cows. The highest percentage of CMT (72%) and WST (59%) positive cases were found in cows having parity number 2. The CMT (71%) and WST (53%) test results were similar in third parity cows. The first parity cows were less prone to mastitis (47%). Mastitis had significantly (P=0.002) negative effect on days required to first heat after parturition. Mastitis was also negatively correlated with calving interval (CI) (P=0.030). More the incidence of mastitis prolongs the calving interval and the highest percentage (85% for CMT and 71% for WST) of mastitis was found in cows having 380-400 days calving interval. Lowest mastitis (54% for CMT and 48% for WST) incidence detected cows lowest calving interval. Significantly, more number of Service per Conception (SPC) was also required in cows having more incidence of mastitis (P=0.03). SPC was 4 for subclinical to clinical cases and 3 for clinical cases. Conclusion: Significant correlation between mastitis and post-partum conception is recorded in this study that may hamper reproductive performances. http://doi.org/10.5455/javar.2017.d203 XML PubReader